Retrospective cohort study of changes in estimated glomerular filtration rate for patients prescribed a low carb diet. Issue 5 (October 2021) - Mitchell, Nia S.; Batch, Bryan C.; Tyson, Crystal C.
Abstract : Purpose of review: Obesity and diabetes contribute to chronic kidney disease (CKD) and accelerate the loss of kidney function. Low carbohydrate diets (LCDs) are associated with weight loss and improved diabetes control. Compared to the typical Western diet, LCDs contain more protein, so individuals with CKD are not included in studies of LCDs. Therefore, there are no studies of LCDs for weight loss and their effects on kidney function. Recent findings: Obesity, hyperglycemia, and hyperinsulinemia can be detrimental to kidney function. LCDs may improve kidney function in patients with obesity and diabetes because they are associated with weight loss, improve blood sugar control, and decrease endogenous insulin production and exogenous insulin requirements. Summary: In this study, for patients with mildly reduced and moderately to severely reduced kidney function who were prescribed an LCD, their estimated glomerular filtration rate (eGFR) was either unchanged or improved. For those with normal or elevated eGFR, their kidney function was slightly decreased. For those without diabetes, greater weight loss was associated with improved eGFR. Future studies should prospectively measure low carbohydrate dietary adherence and physical activity and directly measure changes in GFR and albuminuria for participants with CKD before and during that diet. Abstract : Supplemental Digital Content is available in the text